Lack of Neurosteroid Selectivity at δ vs. γ2-Containing GABAA Receptors in Dentate Granule Neurons - Lu, Xinguo; Zorumski, Charles F.; Mennerick, Steven (Frontiers in Molecular Neuroscience, 2020)
GABAA receptors mediate a large fraction of inhibitory neurotransmission in the central nervous system. Two major classes of GABAA receptors are γ2-containing receptors and δ-containing receptors, which are largely located synaptically and extrasynaptically, respectively. Neuroactive steroids such as allopregnanolone (3α5αP) and allotetrahydrodeoxycorticosterone (THDOC) are hypothesized to selectively affect δ containing receptors over γ2 containing receptors. However, the selectivity of neurosteroids on GABAA receptor classes is controversial. In this study, we re-examined this issue using mice with picrotoxin resistance associated with either the δ or γ2 subunit. Our results show that 3α5αP potentiated phasic inhibition of GABAA receptors, and this is mainly through γ2-containing receptors. 3α5αP, with or without exogenous GABA, potentiated tonic inhibition through GABAA receptors. Surprisingly, potentiation arose from both γ2 and δ-containing receptors, even when a δ selective agonist THIP was used to activate current. Although ethanol has been proposed to act through neurosteroids and to act selectively at δ receptors, we found no evidence for ethanol potentiation of GABAA receptor function at 50 mM under our experimental conditions. Finally, we found that the actions of pentobarbital exhibited very similar effects on tonic current as 3α5αP, emphasizing the broad spectrum nature of neurosteroid potentiation. Overall, using chemogenetic analysis, our evidence suggests that in a cell population enriched for δ-containing receptors, neurosteroids act through both δ-containing and non-δ-containing receptors.